Cyclosporine as a novel treatment for amatoxin-containing mushroom poisoning: a case series. Issue 1 (31st December 2022) - Mackenzie, Constance A.; Austin, Emily; Thompson, Margaret; Tirona, Rommel G.
Abstract: Ingestion of amatoxin-containing mushrooms can lead to fulminant hepatotoxicity and death. Despite recent interest in therapeutic options for amatoxin-exposed patients, there is no single, recommended treatment for amatoxin poisoning. Alpha-amanitin, the principal toxin in amatoxin-containing mushrooms, requires entry into hepatocytes via organic anion transporting polypeptide (OATP) 1B3 before the cascade of cellular events occurs leading to hepatocyte necrosis, liver failure, and in severe cases liver transplantation or death. Three patients managed through a single poison centre with confirmed amatoxin-containing mushrooms ingestions were treated with intravenous cyclosporine, a known potent OATP1B3 inhibitor, along with supportive care. All patients presented with classic delayed symptoms of nausea, vomiting and diarrhea. No patient progressed to fulminant hepatic failure, although two patients developed a transient rise in liver transaminases. All recovered and were discharged from hospital. No patient had an adverse effect from cyclosporine. In addition, we performed an in-vitro study of the role of cyclosporine in cultured HEK293T cells and human hepatoma Huh7 cells. Cyclosporine effectively inhibited OATP1B3-mediated uptake of alpha-amanitin, and improved cell viability of alpha-amanitin exposed cultured Huh7 cells. We conclude that IV cyclosporine, a drug readily available in most hospitals, may be useful to reduce hepatotoxicity from amatoxin poisoning.